Effect of Modified Greenhouse Drying Technology on the Physicochemical Quality of Cameroonian Cocoa Beans - Banboye D. Frederick; Ngwa Martin Ngwabie; Nde Divine Bup (International Journal of Food Science)
Several benefits give credence to the importance of maintaining the reference values of the physicochemical properties of cocoa beans at all stages along the cocoa chain. Every drying method confers significant effects on quality with implications on demand and prices. In this work, the modified greenhouse dryers were tested as potential equipment for the production of high quality cocoa beans. To ascertain their validity for use in the cocoa chain, moisture content, pH, free fatty acid, total polyphenol, peroxide value, total phenols, condensed tannins, and flavonoids were investigated. In relation to reference values, all the samples were of good quality. In terms of moisture content, pH, total acidity, free fatty acid, total polyphenol content, phenol content, flavonoids, and peroxide value, the samples fell within the acceptable values. Total phenols, flavonoids, and condensed tannins were within the recommended range. Samples dried in the open sun dryer and modified greenhouse dryer with fleece of cotton presented the highest amounts of total phenols, flavonoids, and condensed tannins. For total fat content, the samples dried in modified greenhouse dryers equipped with fleece of polyester and the conventional greenhouse dryer were distinctly of grade one quality.